Hubungan Psycap dengan Kinerja Karyawan PT. X Bandung - Iwan Hanafi Liwarto; Albert Kurniawan (Universitas Kristen Maranatha, 2015)
The research of this study is about Psychological Capital (PsyCap) theory that is proposed by Luthans, it is still new and limited theory. Luthans divides Psycap theory into 4 (four) dimensions: Hope, Self-Efficacy, Resiliency, and Optimism. From the previous research, Psycap linked to employee performance.Luthans, Avolio, Avey and Norman (2006) concluded that: There were significant positive effects among four dimensions (Hope, Self-Efficacy, Resiliency, and Optimism) to satisfaction and employee performance. Tjakraatmadja and Febriansyah (2006 and 2007) have investigated the relationship among psycap, the learning environment as external factor (moderator variable) and student GPA (as a performance indicator).The objective of this research is to determine the descriptionof PsyCap and employee performance at PT.X and ultimately to determine whether there is a relationship of Psycap with employee performance. This research is using non-probability method which is Purposive Sampling and it took 66 employees as respondents. The type of this research is using associative research. The result of 66 respondents proved that Psycap of the employee at PT.X Bandung is high and the result of the employee performance is also having high rate. And there is asignificant relationship between employee performance and Psycap simultaneously or partially. Self-Efficacy, Hope, and Resiliency have average, and Optimism have high rate to employee performance.Keywords: Psychological Capital, Employee Capital